Acceptability of a sitting reduction intervention for older adults with obesity - Theresa E. Matson; Anne D. Renz; Michelle L. Takemoto; Jennifer B. McClure; Dori E. Rosenberg (BMC, 2018)
Abstract Background Older adults spend more time sitting than any other age group, contributing to poor health outcomes. Effective behavioral interventions are needed to encourage less sitting among older adults, specifically those with obesity, but these programs must be acceptable to the target population. We explored participant acceptance of a theory-based and technology-enhanced sitting reduction intervention designed for older adults (I-STAND). Methods The 12-week I-STAND intervention consisted of 6 health coaching contacts, a study workbook, a Jawbone UP band to remind participants to take breaks from sitting, and feedback on sitting behaviors (generated from wearing an activPAL device for 7 days at the beginning and mid-point of the study). Semi-structured interviews were conducted with 22 participants after they completed the intervention. Interview transcripts were iteratively coded by a team, and thematic analysis was used to identify and refine emerging themes. Results Overall, participants were satisfied with the I-STAND intervention, thought the sedentary behavior goals of the intervention were easy to incorporate, and found the technologies to be helpful additions to (but not substitutes for) health coaching. Barriers to standing more included poor health, ingrained sedentary habits, lack of motivation to change sedentary behavior, and social norms that dictate when it is appropriate to sit/stand. Facilitators to standing more included increased awareness of sitting, a sense of accountability, daily activities that involved standing, social support, and changing ways of interacting in the home environment. Participants reported that the intervention improved physical health, increased energy, increased readiness to engage in physical activity, improved mood, and reduced stress. Conclusions The technology-enhanced sedentary behavior reduction intervention was acceptable, easy to incorporate, and had a positive perceived health impact on older adults with obesity. Trial registration The I-STAND study was registered at clinicaltrials.gov (ID: NCT02692560) February 2016.